Calorimetry system for heat load in long-pulse discharges on EAST tokamak. (1st September 2022) - Zhuang, Qing; Ming, Tingfeng; Yu, Yaowei; Liu, Yukai; Yang, Lei; Long, Feifei; Shi, Qiqi; Li, Bang; Liu, Shaocheng; Liu, Haiqing; Li, Guoqiang; Gao, Xiang
Abstract: A calorimetry system has been developed in Experimental Advanced Superconducting Tokamak (EAST). It is employed to evaluate the heat load exhausted by cooling water. Full poloidal coverage is achieved after the upgrade in 2019. The experimental results show that the heat load exhausted by cooling water is 64%–86% of the injected energy. Moreover, the heat load increases faster in the case with a higher heating power, and this is qualitatively confirmed by the simulation. In addition, a longer time is required for the temperature of the cooling water to achieve its maximum for a higher heating power. And in the decay phase of the water temperature, it shows an exponential characteristic. The averaged time constant of the thermal decay obtained by exponential fitting for the upper and the lower divertor are 12.1 s and 107.9 s, respectively. It indicates that the heat removal capability of the upper tungsten divertor outperforms the lower graphite divertor.